Design and performance of an enhanced IEEE 802.11 MAC protocol for multihop coverage extension. - Fitzek, F.H.P (IEEE Wireless communications)
Ad hoc communication is gaining popularity, not only for pure ad hoc communication networks but also as a viable solution for coverage extension in wireless networks. Especially for upcoming WLAN hotspots, this is an interesting option to decrease installation costs. In this article we introduce a new MAC protocol that needs only marginal changes to the standard and enables efficient multihop networking. We advocate the use of multiple IEEE 802.11 channels, where one channel is reserved as a common signalling channel for the task of assigning the others (data channels) among wireless terminals. The proposed MAC protocols are based on a four-way handshake over the common signalling channel, while data transmission occurs on a dedicated channel. We propose a further optimization applying multiple wireless network interface cards. This improvement in performance comes at the price of a slightly more complex hardware. Two different simulation models are implemented to investigate our approach. The first model investigates the MAC protocol and its improvements, while the second model analyzes the multihop performance in terms of delivery ratio and transmission delay. BY means of numerous simulations we present the performance of our MAC approach in comparison with two standard approaches in terms of bandwidth, packet delivery, and transmission delay. For our performance evaluation we apply the IEEE 802.11a technology, but we note that our approach can also be used for IEEE 802.11b.